Flow Pump Motor Speed Controller System Using PLC Simatic PCS-7 and PID in PT Sun Paper Source - Prenata, Giovanni Dimas; Baihaqi, Ahmad (BEST, 2025)
Motor speed control can be done using PID. Through the PID tuning process on the Simatic PCS 7 PLC, the values ​​Kp = 6, Ki = 45 and Kd = 8 were obtained as parameters for regulating the rotation speed of the pump motor. PID tuning was previously carried out in Matlab by entering the transfer function equation of the pump motor and then obtaining the constant values ​​Kp = 4, Ki = 12 and Kd = 16 through the PID tuning process. The performance of motor speed control using PID (PLC Simatic PCS 7) is not up to target, this is because the PID tuning process takes place simultaneously with the operation of the PLC as the main controller of the production process.